1970
DOI: 10.3329/bjar.v34i4.5833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvesting stages on the seed quality of lentil (<i>Lens culinaris</i> L.) during storage

Abstract: Laboratory experiments were carried out during August to September 2004 and 2005 at the Seed Technology Laboratory, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh to determine the effects of harvesting stages on the seed quality of lentil. Lentil seeds of three varieties were harvested at three stages at 7-day intervals viz. i) when the pods were yellowish with a few yellow greens (H 1 stage), ii) when most of the pods were light brown with a few yellow (H 2 stage), and iii) when all the pods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 2 publications
6
22
0
5
Order By: Relevance
“…Reddy and Khan (2001) recorded a positive and significant correlation between germination and seedling dry weight (0.68*), vigour index I (0.91**) and vigour index II (0.97**). Similar results were also reported by Khatun et al (2009).…”
Section: Correlationsupporting
confidence: 92%
“…Reddy and Khan (2001) recorded a positive and significant correlation between germination and seedling dry weight (0.68*), vigour index I (0.91**) and vigour index II (0.97**). Similar results were also reported by Khatun et al (2009).…”
Section: Correlationsupporting
confidence: 92%
“…The results are in agreement with the findings of Ayyub et al (2007) who reported that physiologically mature seeds displayed better viability than immature seeds. The results is also conformity with the findings of Khatun et al (2009) who asserted that lentil seeds collected at the stage when most of the pods were light brown with a few yellow (H 2 stage) recorded the highest germination percentage, dry weight, root length, shoot length, seedling length and vigour index (vigour index-I and vigour-Il).…”
Section: Effect Of Harvest Time On the Seed Quality Parameters Of Fresupporting
confidence: 91%
“…Decrease in seedling dry weight was due to nutrients supply from mother plant was restricted to seed due to disruption of vascular connection and utilization in various physiological and metabolic processes (Khatun et al, 2009). These findings are supported by who reported that soybean seedling dry weight decreased in seeds from late sown crop.…”
Section: Resultsmentioning
confidence: 54%